The psychological profile of pilots of passenger planes: Analysis of temperamental traits, aggression and risk - Ryszard Makarowski; Andrzej Piotrowski (Medycyna Pracy, 2017)
Background: Over the years it has been assumed, that the greater the number of pilot flight hours, the better the development of problem-solving skills among pilots. Research suggests, however, that the problem is more complex than that. Not only one’s experience is of importance – temperament, aggression and risk may also affect the decision-making process under stressful conditions. Material and Methods: We examined 97 male pilots of passenger planes, who had flew ATRs, Boeings, Airbuses, Embraers, and Saabs. The comparative group was made up of 127 graduates of technical studies (not connected with aviation). In our study, we used the following methods: the PTS (Pavlovian Temperament Survey) Temperament Questionnaire by Strelau, the Aggression Questionnaire by Buss and Perry, and the Stimulating-Instrumental Risk Inventory (SIRI) by Zaleśkiewicz. Results: Following the analyses we could categorize the pilots into 3 distinct groups: group 1 – strong type of nervous system with a tendency to avoid risk; group 2 – strong type of nervous system with a tendency to take risks; group 3 – the relatively weakest type of nervous system with a tendency toward aggressive behavior. Conclusions: Members of each group were analyzed to assess how they function in a task situation, i.e., whilst piloting a passenger plane. The study showed that individuals with high need for stimulation may – consciously or not – seek situations of excessive or unnecessary risks, and this is done in order to reach the right level of stimulation. A constellation of the following variables: temperament, risk, and aggression could be – we argue – useful in psychological examinations, and should be taken into account in training procedures for pilots. Med Pr 2017;68(5):639–651